2016
DOI: 10.1108/mrr-07-2015-0157
|View full text |Cite
|
Sign up to set email alerts
|

A study of coaching leadership style practice in projects

Abstract: Purpose The purpose of this paper is to describe and discuss how project managers practice a coaching leadership style (CLS). Design/methodology/approach This paper is based on a case study of an organization practicing coaching in projects. Findings The research findings show that to succeed with a CLS, project managers must have a large toolbox, which includes signature strengths, self-management and a give culture. Further, the paper describes how a model consisting of two learning processes can help to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 48 publications
2
82
0
4
Order By: Relevance
“…Nors tyrėjai nustatė tiesioginį ryšį tarp vadovavimo stiliaus ir vadovavimo veiksmingumo, veiksmingumo ir kuriamos gerovės, vis dėlto vadovavimas ir jo stiliai yra neišsenkantys mokslinių tyrimų šaltiniai (Sudha, Shahnawaz, Farhat, 2016: 112). Mokslininkai nuolat ieško geriausių, išskirtinių vadovavimo savybių arba veiksmingiausio vadovavimo stiliaus (Berg, Karlsen, 2016: 1123. Vieni tyrimai nustatė sąsajas tarp vadovavimo stilių ir darbo našumo skirtinguose lygiuose (individualus, grupinis ir organizacijos) bei santykinius vadovavimo būdus, atsižvelgiant į aplinkybes (Sarti, 2014: 205).…”
Section: Vadovavimo Stilių Svarba Ir Sampratosunclassified
See 1 more Smart Citation
“…Nors tyrėjai nustatė tiesioginį ryšį tarp vadovavimo stiliaus ir vadovavimo veiksmingumo, veiksmingumo ir kuriamos gerovės, vis dėlto vadovavimas ir jo stiliai yra neišsenkantys mokslinių tyrimų šaltiniai (Sudha, Shahnawaz, Farhat, 2016: 112). Mokslininkai nuolat ieško geriausių, išskirtinių vadovavimo savybių arba veiksmingiausio vadovavimo stiliaus (Berg, Karlsen, 2016: 1123. Vieni tyrimai nustatė sąsajas tarp vadovavimo stilių ir darbo našumo skirtinguose lygiuose (individualus, grupinis ir organizacijos) bei santykinius vadovavimo būdus, atsižvelgiant į aplinkybes (Sarti, 2014: 205).…”
Section: Vadovavimo Stilių Svarba Ir Sampratosunclassified
“…Šie keturi požymiai pasireiškia transformacinio vadovo veiksmuose (Strom, Sears, Kelly, 2014: 73;Berg, Karlsen, 2016: 1124Fazzi, Zamaro, 2016: 862): 1) idealizuota įtaka, kai vadovas veikia kaip sektinas pavyzdys, su kuriuo tapatinasi darbuotojai; 2) įkvepiantis skatinimas, kai vadovas bendraudamas drąsina, įkvepia ir skatina įsipareigoti; 3) skatinimas mąstyti, kai vadovas diegia naujoves ir skatina darbuotojų kūrybiškumą; 4) asmeninis dėmesys, kai vadovas rūpinasi darbuotojų poreikiais. Transformaciniai vadovai paprastai tampa sektinu pavyzdžiu (Men, Stacks, 2013: 174;Hoten, Brenner, 2015: 3-4), sukuria bendros ateities pojūtį, kelia sekėjų (darbuotojų) pasididžiavimą ir pasitikėjimą, įkvepiančiu vadovavimo stiliumi jiems suteikia daugiau įgaliojimų veikti, skatina juos permąstyti savo nusistovėjusias veiklas ir mąstymo nuostatas, kreipia asmeninį dėmesį į darbuotoją, siekdamas sužinoti kiekvieno poreikius.…”
Section: Vadovavimo Stiliaiunclassified
“…Boal (2000) and Goldman, Cahill and Filho (2009) added the elements of developing strategic thinking, building a vision and motivating others, and receiving coaching and mentoring (Berg & Karlsen, 2016;Goldman, Wesner & Karnchanomai, 2013). This study draws on these propositions as a frame for the research.…”
Section: Facilitators and Inhibitors Of Transitionmentioning
confidence: 99%
“…Despite the growing popularity of coaching-based leadership interventions (Milner et al, 2018), the efficacy of these programs and their impact on the development of effective leaders have rarely been assessed (Ellinger et al, 2011;Grant and Hartley, 2014;Berg and Karlsen, 2016). Indeed, previous research has revealed that only one-third of these initiatives are evaluated (Ely et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that leaders need at least 3 to 6 months to develop coaching skills and feel comfortable using them (Grant, 2010). So far, very little is known about the benefits of developing a coaching-based leadership style and its impact on work-related outcomes (Berg and Karlsen, 2016) such as psychological capital (PsyCap), work engagement and in-role and extrarole performance.…”
Section: Introductionmentioning
confidence: 99%